Transaksi Jual Beli On-Line (Instagram) dengan Akad Salam - Anam, Mohamad Hoirul (Sekolah Tinggi Islam Blambangan Banyuwangi, 2019)
Abstract: In this modern muamalah transaction new technological developments emerged, online buying and selling can be done through social media. Because of the influence of these technologies, it is considered important to examine further the practice of buying and selling on line and the validity of the contract. This is descriptive legal research, data collection is done by reviewing the literature on online buying and selling then analyzed by examining data, data classification and data analysis. His research results illustrate: the practice of buying and selling online through social media was carried out initially opening social media profiles, followed by looking at the products offered 2) Online buying and selling is permissible, harmonious and the terms of buying and selling online do not conflict with harmony and conditions in the legal system of Islamic engagement. 3) Online sale and purchase of greetings in accordance with the MUI DSN Fatwa No. 05 / DSN-MUI / IV / 2000 concerning Sale and Purchase Salam, because the contract does not violate existing Shari'a rules, so that in the future the existence of the Fatwa must be recognized and implemented in this modern economic activity.